Who is Telling 'Australian' Stories? The Results from the First Nations and People of Colour Writers Count. (2nd September 2022) - Kon-yu, Natalie; Booth, Emily
ABSTRACT: The Australian Publishing Industry has long been critiqued for its lack of diverse voices. In Australia movements such as Voices From the Intersection and The Stella Diversity Survey have been aimed at bringing an awareness of this lack to a larger audience, while festivals such as Blak and Bright, and awards such as The Next Chapter, have sought to highlight the works of authors who identify as First Nations or as Writers of Colour. The study discussed in this paper is the first large-scale study that sought to identify how culturally diverse the author cohort was in the study year of 2018. The First Nations and People of Colour Writers Count (henceforth FNPOC Writers Count) sought to identify the publication rate of books in 2018 that were by Australian authors who publicly identified as First Nations people or People of Colour. The purpose of the project was to develop the first large-scale numerical dataset that illustrated the inequity in Australia's publishing industry that has been anecdotally observed for many years.